Frequency of spermatozoa with caspase 3/7 activation obtained from alpaca epididymis analyzed by flow cytometry - Baez Oré, Luis (2023)
The study aimed to determine the proportion of alpaca (Vicugna pacos) sperm cells with caspases-3/7 in an activated form. The epididymis of 23 pairs of testicles obtained from the Municipal Slaughterhouse of Huancavelica, Peru, were used. In the laboratory, an extender (fat-free milk, egg yolk and fructose) was used to obtain sperm cells from the caudal part of the epididymis. The cells were washed twice with 1 mL of PBS and centrifuged. It was added 100 µL of CellEvent™ Caspase 3/7 Green Detection Reagent to the product and incubated at 37.5 °C for 30 min, while 0.5 µL of Propidium Iodide was added 10 minutes before the end of the incubation, as a marker of cell death. The reading was done by flow cytometry. The mean ± standard deviation of sperm cells with caspase 3/7 activation was 36.21 ± 11.25%, confidence interval from 31.34 to 41.08% and a coefficient of variation of 31.07%. The data presented a normal distribution according to the Kolmogorv-Smirnov test. The correlations between spermatozoa with activated caspases 3/7 with the weight and volume of the testis and with sperm motility and concentration were not significant. It is estimated between 31 to 41% of alpaca epididymal spermatozoa are in the process of apoptosis.